Two-dimensional numerical study of isotoxal-star polygonal cylinders in cross-flow. Issue 188 (May 2019) - Lee, Y.J.; Zhou, G.; Lua, K.B.
Abstract: Numerical simulations have been conducted to investigate the flow structures and the force generation of two-dimensional regular and isotoxal-star polygonal cylinders in low Reynolds number (≈150) cross-flow. The isotoxal-star polygons are essentially N -sided regular polygons with the addition of N V-grooves. Generally, transforming the regular polygon into the equivalent isotoxal-star polygon increases the normalized circulation, resulting in an increase in the magnitude of lift fluctuation and mean drag generation; this effect is sensitive to cylinder orientation. The influence of each V-groove on the overall flow structure and force generation of the isotoxal-star polygon is dependent on its placement and orientation, and the V-grooves fall into three main categories. Type I V-grooves are windward facing V-grooves containing the stagnation point; they are generally ineffective at enhancing force generation. Type II V-grooves are those upstream of the separation point but do not contain the stagnation point. They may enhance the magnitude of lift fluctuation if windward oriented, or yield negligible lift enhancement if oriented towards the transverse direction. Type III V-grooves are those downstream of the separation point, and they enhance the magnitude of lift fluctuation if they are oriented towards the vertical direction. Highlights: Numerical study of 2D regular and isotoxal-star polygonal cylinders in low Reynolds number (≈150) cross-flow. The isotoxal-star polygons are essentially N -sided regular polygons with the addition of N V-grooves. The influence of the V-grooves falls into three main categories. Type I V-grooves are windward facing and contain the stagnation point. Generally, they do not enhance force generation. Type II V-grooves are upstream of the separation point. They increase lift fluctuation if windward oriented. Type III V-grooves are downstream of the separation point. They increase lift fluctuation if vertically oriented.